Case report: Kabuki syndrome and persistent hypoglycemia in neonates - Osama Y Safdar; Miral M Abddulghfar; Renad N Saaty; Zahrah Bernawi; Reem Babteen; Osama M Felemban (Journal of Family Medicine and Primary Care)
The Kabuki syndrome (KS) is a rare congenital disease that has two different types, KS1 and KS2, with variant in epigenetic gene KMT2D and KDM6A, respectively. It is associated with multiple abnormalities such as (developmental delay, atypical facial features, cardiac anomalies, minor skeleton anomalies, genitourinary anomalies, and mild to moderate intellectual disability). This syndrome can lead to neonatal hypoglycemia that results from hyperinsulinemia and electrolyte abnormalities. We described 18-month-old Egyptian girl with Kabuki syndrome type 2 presented with persistent hypoglycemia since birth and accompanied by an abnormality in urine concentration, and blood gases showed academia. She was treated medically. The diagnosis was made at the age of five months. Growth failure and developmental delay were noted during the patient’s growth. We found that KS2 with heterozygous gene mutation KDM6A, which had related with severe hypoglycemia in neonates. Mostly due to congenital hyperinsulinism for further investigations. We aim to increase the awareness of different genetic diseases that are related to neonatal hypoglycemia and early recognition and treatment to prevent the neurodevelopmental complication and improve the outcome.